Striking the right balance - Ismail, Noor Azizi (Star Publications (M) Bhd, 2014)
The only business school in Malaysia with a comprehensive pool of faculty members in each and every aspect of business management aims to use this advantage to produce future business leaders with international outlooks,excellent decision making abilities, and the capability to execute changes for the betterment of business, society and the environment.